KEPEMIMPINAN DALAM AL-QUR’AN DAN RELEVANSINYA DI ERA MODERN - Masripah Masripah; Afni Raisya; Ai Atun Mardiah (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2025)
Leadership in the Qur’an emphasizes values such as justice, consultation, trustworthiness, and noble character. The Prophet Muhammad saw serves as the ultimate role model in Islamic leadership, demonstrating how a leader should prioritize public welfare, honesty, and transparency in decision-making. In the modern era, leadership challenges have become more complex due to globalization, technological advancements, and increasing social diversity. The principles of leadership in the Qur’an remain relevant in addressing contemporary issues such as social inequality, corruption, and the crisis of trust in leadership. This paper discusses how Islamic leadership values—such as justice, transparency, public participation, and sustainability—can be applied in the modern context to create effective, ethical, and welfare-oriented leadership. As globalization continues to influence leadership in all aspects, adopting Qur’anic leadership principles is essential to navigating modernization. By implementing these teachings, modern leaders can manage contemporary complexities while fostering inclusive governance and societal well-being.